Action Situation Perilaku Merokok di Kawasan Tanpa Rokok Fakultas Kesehatan Masyarakat Universitas Airlangga - Eka Yeyen Pertiwi; Sri Widati (Jurnal Keperawatan Muhammadiyah, 2019)
Smoking is an unhealthy behavior. According to The Tobacco Atlas 5th edition, Indonesia ranked 4th in the world in terms of cigarette consumption. There needs to be efforts to control smokers and protect non-smokers. One of the efforts to control the impact of cigarettes is the Non-Smoking Area. The results of the archipelagic study that has been carried out, smoking behavior is still carried out both by students, employees and lecturers at the non-smoking area Faculty of Public Health.The research design used was a quantitative observational approach with a cross sectional study design. The study was conducted at the Public Health Faculty of Universitas Airlangga, Surabaya. Respondents of this study were aged 18-59 years with all male gender. Respondents are FKM UNAIR academics who smoke. Based on the results of the study and analysis, the results of the statistical test chi square variable action situation with the results of fisher's exact smaller than alpha which means significant.The results of this study are that there is a correlation between smoking behavior and action situation. Action situations are situations that support respondents to smoke.Suggestions for faculties are to conduct evaluations and checks on traders in the faculty who are still selling cigarettes. Give sanctions to traders who still sell cigarettes. Issue technical regulations for the implementation of Non-Smoking Areas in FKM in writing and based on existing non-smoking area regulations. Form a field supervisor team related to non-smoking Area implementation directly. Form a counseling consulting team to stop smoking.